(untitled) (Eurasian Medical Research Periodical, 2022)
The examinations were carried out in 34 patients in the period of acute remission and remission of kasallik in patients with SOVID-19, aged 22 to 70 years. The diagnosis of COVID -19 was confirmed by clinical, epidemiological and laboratory (PTSR) method. Currently, there is an increase in the number of cases of Lymphocytoplarning and the absolute number of cases of T-helperlar-SD4+ and T-killerlar-SD8+ quantitative assessment of absolute and relative births